Alterations of color vision and pupillary light responses in age-related macular degeneration - Decleva, Diego; Vidal, Kallene Summer; Kreuz, Andre Carvalho; de Menezes, Paulo Augusto Hidalgo Leite; Ventura, Dora Fix (Frontiers in Aging Neuroscience, 2023)
Introduction. Age-related macular degeneration (AMD) is the leading cause of irreversible central vision loss in developed countries and one of the leading causes of blindness. In this work, we evaluated color vision and the pupil light reflex (PLR) to assess visual function in patients with early and neovascular AMD (NVAMD) compared to a control group. Methods. We recruited 34 early dry AMD, classified as 2 by AREDS, and 13 NVAMD patients, and 24 healthy controls. Control and early dry AMD patients had visual acuity best or equal to 20/25 (0.098 logMAR). Color vision was assessed in Control and early dry AMD using the Cambridge Color Test 2.0 through the Trivector protocol. The PLR was evaluated using a Ganzfeld, controlled by the RETI–port system. The stimuli consisted of 1s blue (470 nm) and red (631 nm) light flashes presented alternately at 2 min intervals. To assess the cones’ contribution, we used a red flash at 2.4 log cd.m-2 with a blue background at 0.78 log cd.m-2. For rods, we used 470 nm flashes at -3 log cd.m-2 and for the melanopsin function of ipRGCs we used 470 nm at 2.4 log cd.m-2. Results. Early dry AMD patients had reduced color discrimination in all three axes: protan (p=0.0087), deutan (p=0.0180) and tritan (p=0.0095), when compared to the control group. The PLR has also been affected in patients with early dry AMD and patients with NVAMD. The response amplitude for melanopsin-driven response was smaller in early (p=0.0485) and NVAMD (p=0.0035) when compared to the control group. The melanopsin function, was lower in patients with NVAMD (p=0.0290) when compared to the control group. For the rod-driven response, the latency was slower for the NVAMD group (p=0.0041) when compared to the control group. No changes were found in cone-driven responses between the control and AMD groups. Conclusions. Patients with early dry AMD present diffusely acquired color vision alteration detected by CCT. Rods and melanopsin contributions for PLR are affected in NVAMD. The CCT and the PLR may be considered sensitive tests to evaluate and monitor functional changes in AMD patients.